The ghost army of World War II how one top-secret unit deceived the enemy with inflatable tanks, sound effects, and other audacious fakery - Beyer, Rick 1956- (Princeton Architectural Press, 2015)
A cultural history/visual culture book featuring the story, photos, ephemera, and art of The Ghost Army, a World War II deception unit, which used inflatable tanks and other illusions to mislead the Germans on the battlefields of Europe. The Army recruited artists to create these illusions; in private moments, they painted and sketched their way across Europe, creating a unique visual record of the war